Anxiety in Relatives of Patients Admitted to Cardiac Care Units and its Relationship with Spiritual Health and Religious Coping - Fereshteh Dehghanrad; Marjan Mosallanejad; Marzieh Momennasab (Universidad de Antioquia, 2020)
Objective. This work sought to determine the level of anxiety in relatives of patients admitted to CCUs and its relationship with spiritual health and religious coping. Methods. This cross-sectional study was conducted on 300 relatives of Cardiac Care Units patients in Jahrom, Iran. Required data was collected using the Spielberger State-Trait Anxiety Inventory (STAI), the Paloutzian-Ellison Spiritual Well Being Scale (SWBS), and the Pargament Brief RCOPE questionnaire. Results. The results showed that both levels of state and trait anxiety were moderate and the level of total spiritual health was high. Anxiety score had an inverse relationship with spiritual health (r=-0.52) and a direct relationship with negative religious coping score (r=0.25). However, no significant relationship was found between total anxiety score and positive religious coping (p>0.05). There was a direct relationship between spiritual health and positive religious coping (r=0.19), and an inverse relationship between spiritual health and negative religious coping (r=-0.36). Conclusion. According to the findings of the study, it is suggested to paying attention to the reinforcement of spiritual attitudes, beliefs, and religious coping strategies to reduce their anxiety in CCU patients.